Insights into the length and breadth of methodologies harnessed to study human telomeres - Tiernan Coulter; Claire Hill; Amy Jayne McKnight (BMC, 2024)
Abstract Telomeres are protective structures at the end of eukaryotic chromosomes that are strongly implicated in ageing and ill health. They attrition upon every cellular reproductive cycle. Evidence suggests that short telomeres trigger DNA damage responses that lead to cellular senescence. Accurate methods for measuring telomeres are required to fully investigate the roles that shortening telomeres play in the biology of disease and human ageing. The last two decades have brought forth several techniques that are used for measuring telomeres. This editorial highlights strengths and limitations of traditional and emerging techniques, guiding researchers to choose the most appropriate methodology for their research needs. These methods include Quantitative Polymerase Chain Reaction (qPCR), Omega qPCR (Ω-qPCR), Terminal Restriction Fragment analysis (TRF), Single Telomere Absolute-length Rapid (STAR) assays, Single TElomere Length Analysis (STELA), TElomere Shortest Length Assays (TESLA), Telomere Combing Assays (TCA), and Long-Read Telomere Sequencing. Challenges include replicating telomere measurement within and across cohorts, measuring the length of telomeres on individual chromosomes, and standardised reporting for publications. Areas of current and future focus have been highlighted, with recent methodical advancements, such as long-read sequencing, providing significant scope to study telomeres at an individual chromosome level.